Effects of bile acids on production performance, serum biochemistry, lipid metabolism, and intestinal morphology in broilers - Liu, Wenjing; Li, Xinan; Zhang, Yunlong; Li, Tao; Wei, Yuqiang; Yuan, Xuejun; Li, Yang; Yang, Weiren; Jiao, Ning (Frontiers in Veterinary Science, 2025)
The objective of the present study was to evaluate the effects of exogenous bile acids (BAs) on production performance, serum biochemistry, lipid metabolism, and intestinal morphology in broilers. A total of 20,000 one-day-old Arbor Acres broilers were randomly assigned to two treatment groups, with eight replicates of 1,250 chicks each, for a duration of 42 days. The control group broilers were provided with normal drinking water, while the treatment group broilers were provided with drinking water supplemented with 100 mL of BAs per ton. The results showed that BAs supplementation significantly decreased abdominal fat yield (p < 0.05), while having no significant effect on other slaughter characteristics (p > 0.05). In addition, BAs supplementation significantly decreased serum acrylic aminotransferase concentrations (p < 0.05). Moreover, BAs supplementation also significantly decreased the mRNA expression of lipogenesis-related genes (p < 0.05) and increased the mRNA expression of lipolysis-related genes in the liver (p < 0.05). Furthermore, BAs supplementation significantly improved jejunal morphology by increasing jejunum villus height (VH) (p < 0.05). In summary, BAs supplementation improved production performance, serum enzyme activity, lipid metabolism, and intestinal morphology in broilers, providing a theoretical basis for the application of BAs in broiler production.